1961
DOI: 10.1002/ange.19610731303
|View full text |Cite
|
Sign up to set email alerts
|

Messung von Adsorptionsisothermen an Katalysatoren bei hohen Temperaturen mit Hilfe der Gas‐Festkörper‐Eluierungschromatographie

Abstract: Die Hochtemperatur-Gaschromatographie an Festkorpern wird zur Messung von Adsorptionsisothermen fur Benzol und Hexan a n Silicagel, Tonerdegel und einem SiOsA120~-Crack-Katalysator im Temperaturbereich von 300-550 OC herangezogen. Aus d e n Adsorptionsisosteren werden die Adsorptionswarmen berechnet, Es wird gezeigt, daO die Eluierungs-Gaschromatographie ein auch bei hohen Temperaturen brauchbares Hilfsmittel zur Untersuchung der Adsorption a n Katalysatoren ist. Die obere Temperaturgrenze wird allein durch di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1965
1965
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…This method of deriving isotherm data from the profile of the diffuse boundary of an overloaded elution band in GSC is known as elution by characteristic point method (ECP). ECP was introduced by Cremer, Huber, and Keulemans (11,12).…”
Section: Aşki̇n and İnelmentioning
confidence: 99%
“…This method of deriving isotherm data from the profile of the diffuse boundary of an overloaded elution band in GSC is known as elution by characteristic point method (ECP). ECP was introduced by Cremer, Huber, and Keulemans (11,12).…”
Section: Aşki̇n and İnelmentioning
confidence: 99%
“…Chromatography, is firmly established as an essential technique for physicochemical investigations [9][10][11][12][13][14], however, research by the liquid chromatographic method on adsorption of binary mobile phases solutions, has not considered the most used in the HPLC practice stationary phases: hydrophobic and hydrophilic silicagel. HPLC can be successfully applied to determine adsorption isotherms [6,7,9,12,[15][16][17], by different procedures [18] which lead to practically identical results [19,20] and it has been demonstrated that in the case of adsorbents used in HPLC, the derived adsorption data are in good agreement [8,9,18,21] with those obtained by using the static methods [2,22] for adsorption studies. A common feature of the HPLC procedures is speed.…”
Section: Introductionmentioning
confidence: 76%
“…An easy and simple method to measure the adsorption isotherms for pure components is the ECP method suggested by Cremer and Huber [45]. This method evaluates chromatograms recorded after injecting samples of large size on a column.…”
Section: The Elution By Characteristic Point Methods (Ecp)mentioning
confidence: 99%